Identifikasi Tema Moderasi Beragama dalam Pendidikan Agama Katolik pada Kurikulum Merdeka - Joshua Jolly Sucanta Cakranegara (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2024)
This article aims to describe the identification of the theme of religious moderation in Catholic Religious and Moral Education in the Merdeka Curriculum. This research is a qualitative research using descriptive method and literature study as data collection technique. The results of the study show that at the primary and secondary education levels (Elementary School, Junior High School, and Senior High School), which are divided into six phases, the theme of religious moderation is contained in the elements of learning outcomes in Catholic Religious and Moral Education. In phase A to phase C (Elementary School), the theme of religious moderation is contained in the content of living in harmony and mutual cooperation; appreciate the community traditions; and recognize themselves as citizens of the world. In phase D (Junior High School), the theme of religious moderation is contained in the content of faith by building brotherhood with all people based on the attitude of the Catholic Church towards other religions and beliefs. Finally, in phase E to phase F (Senior High School), the theme of religious moderation is contained in the content of respecting diversity in society as a gift from god, building dialogue and cooperation between people of religions and beliefs and playing a role in the development of the Indonesian nation.